Pelatihan Peningkatan Kemampuan Meta Level Reflection dan Critical Thinking - Hardinanto, Eko; Faizi, Ahmad; Kholifatu Amalia S., Arisni; Prihatin, Yulianah; Mei Diastuti , Indah; Fatkhur Rizal , Muhammad; Setya Nugraha, Alfian (LP3M IAIFA Kediri, 2025)
Abstract This community service aims to provide knowledge for teachers in improving Meta-Level Reflection and Critical Thinking Skills in MTs. Al-Amin Krian Sidoarjo Teachers to adapt and innovate in facing ever-changing challenges. Many teachers and students have not been able to correct their own mistakes, cannot determine which future should be done best because there is no ability to assess their own shortcomings, that is what must be honed in education by improving Meta-Level Reflection. The ability to critically evaluate information, understand the ethical implications of technology, and use technology responsibly and productively is part of Critical Thinking. So, critical thinking is a person's ability to critically analyze a situation, information, or problem, then make decisions or solutions based on logical and rational thinking. Armed with Meta-Level Reflection and Critical Thinking skills, it is hoped that teachers can help create an Indonesian society that is not only familiar with technology, careful in using it in this era of disruption and capable and has the awareness to correct their shortcomings. This will create a society that has hard skills and soft skills.